Diaphragm and preparation method thereof
By adopting a multi-layer separator structure in lithium batteries, using ceramic materials and modified polymer layer materials, the problem of excessive temperature during short circuit of lithium batteries is solved, and the safety and energy density of the battery are protected.
Patent Information
- Application Number
- CN202411864335.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art cannot effectively protect the battery when the lithium battery is short-circuited, resulting in excessive surface temperature and serious risk of medical accidents. At the same time, the protection method of external fuses or positive temperature coefficient materials increases the battery volume and reduces the energy density.
A separator composed of ceramic material, modified polymer layer material and composite slurry is used to contact the positive electrode sheet through the first isolation layer, the third isolation layer comes into contact with the negative electrode sheet, and the second isolation layer is located between the two, forming a multi-layer separator structure to prevent short circuit.
Effectively reduce the temperature increase of lithium batteries in the case of short circuit, prevent internal short circuits and failures of the battery, maintain the safety and energy density of the battery, and avoid the occurrence of medical accidents.
Smart Images

Figure CN119695399A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a diaphragm and a preparation method thereof. Background Art
[0002] Capsule endoscopes are increasingly using lithium batteries as their power source. However, the surface temperature of lithium batteries exceeds 120°C in the event of a short circuit. If a short circuit occurs during the operation of a capsule endoscope, its surface temperature will far exceed the limit that the human body can withstand.
[0003] In the prior art, lithium batteries generally use external fuses or positive temperature coefficient materials to deal with short circuit problems. Although this approach can provide certain protection, it also inevitably increases the overall volume of the battery. The increase in the overall volume of the battery will reduce the volume energy density of the battery. For devices such as capsule endoscopes that have extremely high volume utilization and energy requirements, external protection methods are not applicable. Once a lithium battery short-circuit occurs during operation, it will cause serious medical accidents and pose a major threat to the safety of patients. Summary of the invention
[0004] The main purpose of the present invention is to provide a diaphragm and a preparation method thereof, so as to solve the problem in the prior art of protecting the lithium battery and preventing the lithium battery from short circuiting during operation without increasing the overall volume of the lithium battery.
[0005] In order to achieve the above object, according to one aspect of the present invention, a diaphragm is provided, comprising:
[0006] A first isolation layer, used for contacting with the positive electrode of the lithium battery;
[0007] A third isolation layer, used for contacting with the negative electrode sheet of the lithium battery;
[0008] A second isolation layer is provided between the first isolation layer and the third isolation layer;
[0009] The first isolation layer comprises a ceramic material, the second isolation layer comprises a polymer layer material, and the third isolation layer comprises a modified polymer composite layer material.
[0010] Furthermore, the third isolation layer is obtained by coating the composite slurry on the surface of the second isolation layer.
[0011] Furthermore, the components of the composite slurry include a solvent and a solute, and the solute includes chemically modified modified polymer layer microspheres, a binder, a thickener, and a dispersant;
[0012] Among them, the method for modifying the thermal sensitivity of the polymer layer microspheres is surface modification, or changing the degree of polymerization of the polymer layer microspheres.
[0013] Furthermore, the method for modifying the adhesiveness of the adhesive is any one of copolymerization modification and cross-linking treatment of the adhesive;
[0014] The method of modifying the thickening property of the thickener is to change the molecular weight of the thickener or to modify the structure of the thickener;
[0015] The method for modifying the dispersibility of the dispersant is to adjust any one of the initiator and the chain transfer agent of the dispersant, wherein the initiator and the chain transfer agent are used to change the molecular weight and molecular weight distribution of the dispersant.
[0016] Furthermore, the polymer layer microspheres are any one of polypropylene, polyethylene, polyvinyl chloride, polyethylene terephthalate, and polystyrene.
[0017] Furthermore, the binder is any one of polyvinylidene chloride, polyacrylic acid, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl alcohol, and polytetrafluoroethylene.
[0018] Further, the ratio of solute to solvent is 1:1 to 1:9.
[0019] Furthermore, the thickener is any one of sodium alginate, mica, carboxymethyl cellulose and polyurethane.
[0020] Furthermore, the proportion of the composite slurry is: the mass percentage of the modified polymer layer microspheres is 70%-99.99%, the mass percentage of the binder is 0%-10%, the mass percentage of the thickener is 0%-10%, and the mass percentage of the dispersant is 0%-10%.
[0021] According to another aspect of the present invention, a method for preparing a diaphragm is provided. The method is applied to the above-mentioned lithium battery, and the method comprises:
[0022] A third isolation layer is prepared, wherein the preparation method of the third isolation layer comprises:
[0023] Mixing the modified polymer microspheres, the dispersant and the solvent to obtain a first mixed slurry;
[0024] Adding a binder and a thickener to the first mixed slurry and mixing them to obtain a second mixed slurry;
[0025] adding the binder again into the second mixed slurry;
[0026] The second mixed slurry is coated on the surface of the second insulating layer, and dried and cut within a preset temperature range to obtain a modified polymer composite layer to obtain a third insulating layer. The preset temperature range is 37° C. to 85° C.
[0027] Applying the technical solution of the present invention, the diaphragm provided in the present application is composed of three layers in total, each layer has different materials, and the diaphragm in the present application can be applied to primary batteries such as but not limited to lithium-manganese dioxide batteries, lithium-carbon fluoride batteries, lithium / iron disulfide batteries, lithium-thionyl chloride batteries, and also includes secondary batteries such as lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium iron phosphate, nickel cobalt aluminum ternary, nickel cobalt manganese, etc.;
[0028] The diaphragm in the present application includes a first isolation layer in contact with the positive electrode sheet of the lithium battery, a third isolation layer in contact with the negative electrode sheet of the lithium battery, and a second isolation layer provided between the first isolation layer and the third isolation layer. In the battery, especially in the winding or lamination process, mechanical stresses, including extrusion, friction and impact, will be generated between the positive and negative electrode sheets and in contact with the diaphragm. From a microscopic structural point of view, the ceramic material, due to its own lattice structure and high density, can effectively resist the positive electrode burrs from piercing the diaphragm, protect the diaphragm from damage, and thus reduce the risk of short circuit;
[0029] In addition, the high thermal stability and low thermal expansion coefficient of ceramic materials enable them to maintain structural integrity and stability under high temperature conditions inside the battery. When the battery is charged, short-circuited or thermally runaway, the first isolation layer can withstand high temperatures and avoid shrinkage or melting of the diaphragm due to thermal expansion, thereby preventing internal short circuits and battery failures. The first isolation layer can form a thermal protection barrier inside the battery to prevent high temperatures from directly damaging the third isolation layer, while reducing the speed at which heat from the battery is conducted to the outside world, protecting the battery and external equipment from thermal damage. At the same time, due to the microstructure of the first isolation layer, it can prevent direct contact between the positive and negative active materials inside the lithium battery, and can effectively prevent short circuits even when the internal pressure of the battery changes or minor mechanical damage occurs, thereby ensuring the safe operation of the battery.
[0030] Thermal runaway is a major threat to battery safety. It is usually caused by internal short circuit, overcharging or external overheating, which causes the battery temperature to rise sharply. The heat dissipation capacity of the third isolation layer can dissipate the heat in time, reduce the internal temperature of the battery, and reduce the possibility of thermal runaway. It also helps to reduce the overall temperature inside the battery, especially to avoid overheating of the second isolation layer. Because the second isolation layer includes polymer materials, it has pores. Inside the battery, these pores can promote the flow of gas and form convection channels. When heat is generated inside the battery, convection can accelerate the distribution and dissipation of heat, play a role in heat conduction, and reduce the risk of local overheating of the battery; when the temperature inside the battery is too high, the heat generated by the battery can melt the third isolation layer, block the pores in the second isolation layer, and thus close the ion transmission channel in the second isolation layer.
[0031] The use of external fuses or positive temperature coefficient materials in the prior art can reduce the short circuit hazard to a certain extent, but it will increase the volume and mass of the battery and affect the energy density. This method is not ideal, especially for devices such as capsule endoscopes that have strict requirements on volume and energy density. The technical solution in this application, through the improvement of the internal diaphragm, can not only effectively control the short circuit temperature rise, but also does not require additional volume, which is a more efficient and safe short circuit protection method. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0033] Figure 1 An internal schematic diagram of a lithium battery provided according to the present invention is shown;
[0034] Figure 2 The schematic diagram of the structure of the diaphragm provided by the present invention is shown;
[0035] Figure 3 A temperature comparison diagram when a battery is short-circuited is shown between a separator prepared by the present application and a separator not prepared by the present application.
[0036] The above drawings include the following reference numerals:
[0037] 1. Battery casing; 2. Winding core; 3. First isolation layer; 4. Third isolation layer; 5. Second isolation layer; 6. Positive electrode tab; 7. Negative electrode tab. DETAILED DESCRIPTION
[0038] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0039] Capsule endoscopes are increasingly using lithium batteries as their power source. However, the surface temperature of lithium batteries exceeds 120°C in the case of a short circuit. If a short circuit occurs during the operation of a capsule endoscope, its surface temperature will far exceed the limit that the human body can withstand.
[0040] At present, lithium batteries generally use external fuses or positive temperature coefficient materials to deal with short circuit problems. Although this approach can play a certain protective role, it also inevitably increases the overall volume of the battery, thereby reducing the battery's volume energy density. There is a lack of effective short-circuit protection measures for capsule endoscopes. Once a battery short circuit occurs, it may cause serious medical accidents and pose a major threat to patient safety.
[0041] Therefore, the present application is to address the above problems and provide a diaphragm and a method for preparing the same.
[0042] The present application first provides a diaphragm, comprising: a first isolation layer 3, used for contacting with a positive electrode sheet of a lithium battery;
[0043] The third isolation layer 4 is used for contacting with the negative electrode of the lithium battery;
[0044] A second isolation layer 5 is provided between the first isolation layer 3 and the third isolation layer 4;
[0045] Among them, the first isolation layer 3 includes ceramic material, the third isolation layer 4 includes modified polymer composite layer material, the second polymer layer material, and the third isolation layer 4 includes modified polymer composite layer material.
[0046] Specifically, Figure 1 and Figure 2 As shown, the structure of the lithium battery provided in the present application includes a battery shell 1, a winding core 2 is provided inside the battery shell 1, the winding core 2 includes a positive electrode sheet, a negative electrode sheet and a diaphragm, and the battery shell 1 can be connected to one of the electrode sheets, and the diaphragm is arranged between the positive electrode sheet and the negative electrode sheet to isolate the positive electrode sheet from the negative electrode sheet. At the same time, the winding core 2 in the present application also includes a positive electrode ear 6 and a negative electrode ear 7, one end of all the positive electrode sheets can be brought together through a bus bar to form a first contact end, the positive electrode ear 6 is connected to the first contact end, and all the negative electrode ears 7 are away from the first contact One end of the terminal can be gathered together through a busbar to form a second contact terminal, the negative pole ear 7 is connected to the second contact terminal, and also includes a cover group, the cover group includes a first cover sheet and a second cover sheet connected to the battery housing 1, the first cover sheet is provided with a first through hole for exposing the positive pole ear 6, the positive pole ear 6 can extend to the outside through the first through hole and be connected to other equipment to achieve power supply, and the second cover sheet is provided with a second through hole for exposing the negative pole ear 7, the negative pole ear 7 can be connected to other equipment outside through the second through hole to achieve power supply, wherein, Figure 2 As shown, the diaphragm in the present application includes a first isolation layer 3 in contact with the positive electrode sheet of the lithium battery, a third isolation layer 4 in contact with the negative electrode sheet of the lithium battery, and a second isolation layer 5 arranged between the first isolation layer 3 and the third isolation layer 4. Inside the battery, especially in the winding or lamination process, mechanical stress will be generated between the positive and negative electrode sheets and in contact with the diaphragm, including extrusion, friction and impact. From a microstructural point of view, the ceramic material, due to its own lattice structure and high density, can effectively resist the positive electrode burr piercing the diaphragm, protect the diaphragm from damage, and thus reduce the risk of short circuit;
[0047] In addition, the high thermal stability and low thermal expansion coefficient of the ceramic material enable it to maintain structural integrity and stability in the high temperature environment inside the battery. When the battery is charged, short-circuited or thermally runaway, the first isolation layer 3 can withstand high temperatures and avoid shrinkage or melting of the diaphragm due to thermal expansion, thereby preventing internal short circuits and battery failures. The first isolation layer 3 can form a thermal protection barrier inside the battery to prevent high temperatures from directly damaging the third isolation layer 4, while reducing the speed at which heat from the inside of the battery is conducted to the outside world, protecting the battery and external equipment from thermal damage. At the same time, due to the microstructure of the first isolation layer, it can prevent direct contact between the positive and negative active materials inside the lithium battery, and can effectively prevent short circuits even when the internal pressure of the battery changes or minor mechanical damage occurs, thereby ensuring the safe operation of the battery.
[0048] Thermal runaway is a major threat to battery safety. It is usually caused by internal short circuit, overcharging or external overheating, which causes the battery temperature to rise sharply. The heat dissipation capacity of the third isolation layer 4 can dissipate the heat in time, reduce the internal temperature of the battery, and reduce the possibility of thermal runaway. At the same time, it also helps to reduce the overall temperature inside the battery, especially to avoid overheating of the second isolation layer 5. Because the second isolation layer 5 includes polymer materials, it has pores. Inside the battery, these pores can promote the flow of gas and form convection channels. When heat is generated inside the battery, convection can accelerate the distribution and dissipation of heat, play a role in heat conduction, and reduce the risk of local overheating of the battery; when the temperature inside the battery is too high, the heat generated by the battery can melt the third isolation layer 4, block the pores in the second isolation layer 5, and thus close the ion transmission channel in the second isolation layer 5.
[0049] The use of external fuses or positive temperature coefficient materials in the prior art can reduce the short circuit hazard to a certain extent, but it will increase the volume and mass of the battery and affect the energy density. This method is not ideal, especially for devices such as capsule endoscopes that have strict requirements on volume and energy density. The technical solution in this application, through the improvement of the internal diaphragm, can not only effectively control the short circuit temperature rise, but also does not require additional volume, which is a more efficient and safe short circuit protection method.
[0050] In addition, the diaphragm in the present application can be applied to primary batteries including but not limited to lithium-manganese dioxide batteries, lithium-carbon fluoride batteries, lithium / iron disulfide batteries, lithium-thionyl chloride batteries, and the like, and also includes secondary batteries such as lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium iron phosphate, nickel cobalt aluminum ternary, nickel cobalt manganese, etc.;
[0051] The diaphragm in the present application solves the problem of excessive short-circuit temperature rise of the lithium battery of the capsule endoscope. When the battery is short-circuited, the diaphragm can react quickly to reduce the short-circuit temperature rise to less than 50°C. In addition, the present application forms a diaphragm by providing an isolation layer with different materials, thereby providing battery short-circuit protection without introducing an external device, without changing the battery volume and without reducing the overall energy density of the battery.
[0052] Furthermore, the third isolation layer 4 is obtained by coating the composite slurry on the surface of the second isolation layer 5 .
[0053] Specifically, when making the third isolation layer 4, the composite slurry needs to be coated on the surface of the second isolation layer 5 and dried to obtain the third isolation layer 4, wherein the modified polymer microspheres, binders, thickeners, dispersants and solvents in the composite slurry, after coating and drying, form a uniform third isolation layer 4. This layer of material can enhance the overall mechanical strength, thermal stability and electrolyte compatibility of the diaphragm, thereby improving the safety and service life of the battery.
[0054] Furthermore, the components of the composite slurry include a solvent and a solute, and the solute includes chemically modified modified polymer layer microspheres, a binder, a thickener, and a dispersant;
[0055] Among them, the method for modifying the thermal sensitivity of the polymer layer microspheres is surface modification, or changing the degree of polymerization of the polymer layer microspheres.
[0056] Specifically, when modifying the thermal sensitivity of the polymer layer microspheres by surface modification, compounds having thermal stability groups such as silane groups can be selected as surface modifiers to change the thermal sensitivity of the polymer layer microspheres so as to improve the thermal sensitivity of the polymer layer microspheres; when improving the thermal sensitivity of the polymer layer microspheres by changing the degree of polymerization, the degree of polymerization of the polymer layer microspheres can be adjusted by controlling the polymerization regulation of the polymerization reaction, such as reaction temperature, time, etc., so as to increase the degree of polymerization, because an increase in the degree of polymerization means an increase in thermal stability, and an increase in thermal stability means that when the battery is short-circuited or at high temperature, the diaphragm can be prevented from melting and shrinking, thereby being able to Effectively reduce the risk of thermal runaway. Specifically, when the battery is short-circuited or at high temperature, if the thermal stability of the third isolation layer 4 is poor, it will soften or even melt. After melting, the entire diaphragm will lose its original pore structure and mechanical strength, resulting in direct contact between the positive and negative electrodes of the battery, thereby causing a more serious short-circuit accident. At the same time, due to the softening or melting of the diaphragm, the porosity will be reduced, which will also affect the electrochemical properties of the battery, and may also cause the battery to overheat, increasing the risk of thermal runaway. Therefore, the third isolation layer 4 with enhanced thermal stability can still maintain its physical form and structure, as well as porosity at high temperatures, avoid softening and melting, and thus reduce the risk of short circuit.
[0057] Furthermore, the method for modifying the adhesiveness of the adhesive is any one of copolymerization modification and cross-linking treatment of the adhesive;
[0058] The method of modifying the thickening property of the thickener is to change the molecular weight of the thickener or to modify the structure of the thickener;
[0059] The method for modifying the dispersibility of the dispersant is to adjust any one of the initiator and the chain transfer agent of the dispersant, wherein the initiator and the chain transfer agent are used to change the molecular weight and molecular weight distribution of the dispersant.
[0060] Specifically, the main methods for modifying the adhesiveness of the binder are copolymerization modification or cross-linking treatment. When copolymerization modification is used, its main purpose is to form covalent bonds or hydrogen bonds on the surface of the binder to increase the bonding strength between the binder and other materials, so as to maintain the stability of the internal structure of the battery, reduce the risk of short circuit, and improve the safety of the battery under extreme conditions. At the same time, the strong adhesion between the binder and other materials reduces the shedding of active substances and prolongs the cycle life of the battery. When cross-linking treatment is used, its main purpose is to introduce a cross-linking agent into the binder so that the molecular chains of the binder are connected by chemical bonds (such as covalent bonds) to form a mesh structure or a three-dimensional grid. The cross-linking treatment can enhance the mechanical strength of the binder to ensure the stability of the battery structure. At the same time, the cross-linking treatment can also adjust the porosity of the binder, optimize the contact between the electrolyte and the electrode material, and improve ion transmission, thereby improving the electrochemical performance and energy efficiency of the battery.
[0061] The thickening property of the thickener may be modified by changing the molecular weight of the thickener or modifying the structure of the thickener;
[0062] When the modification method is to change the molecular weight of the thickener, because the molecular weight of the thickener can directly affect its rheological properties in the solution, the thickener with a higher molecular weight has a longer molecular chain and can form more entanglement points. These entanglement points can interact with each other in the solution to increase the viscosity of the solution. At the same time, the thickener with a higher molecular weight can keep the slurry stable for a long time and reduce particle sedimentation. When coating, a uniform coating can be formed to avoid uneven phenomena during the coating process, such as streaks, bubbles or uneven thickness;
[0063] When the modification method is to modify the structure of the thickener, the main methods include introducing hydrophilic or hydrophobic groups, changing the branching degree of the molecular chain or introducing reactive groups, etc. These structural modification methods can change the solubility, dispersibility and reactivity of the thickener in the solution, thereby affecting the thickening effect of the thickener, so as to improve the applicability of the thickener and other components in the slurry;
[0064] The method for modifying the dispersibility of the dispersant is to adjust any one of the initiator and chain transfer agent of the dispersant to change the molecular weight and molecular weight distribution of the dispersant; when the method is to adjust the initiator of the dispersant, because the initiator is the initiator of the polymerization reaction, it can initiate the polymerization reaction of the monomer to form a polymer molecular chain. Different types and concentrations of initiators will affect the mechanism and rate of the polymerization reaction, thereby affecting the molecular weight and molecular weight distribution of the final polymer (dispersant). Dispersants with higher molecular weights can form denser entanglements in the slurry due to their longer molecular chains, thereby improving the wrapping and stabilizing effect on the particles, thereby improving the dispersion efficiency, making the particles in the slurry more uniform and reducing agglomeration. At the same time, the adjustment of the molecular weight and molecular weight distribution can optimize the rheological properties of the slurry, so that it has better operability and stability in processes such as coating and injection, and reduces energy consumption and material waste in the process.
[0065] Furthermore, the polymer layer microspheres are any one of polypropylene, polyethylene, polyvinyl chloride, polyethylene terephthalate, and polystyrene.
[0066] Specifically, polypropylene is selected because it has a high melting point and good thermal stability, and can maintain structural stability within the operating temperature range of the battery to prevent the diaphragm from melting. At the same time, polypropylene has good thermal stability to the chemicals in the electrolyte and is not easily corroded or degraded, thereby extending the service life of the diaphragm. For polyethylene, due to its own low density characteristics, the final diaphragm is relatively light and thin, which is beneficial to improving the energy density of the battery. At the same time, polyethylene is also an insulating material that can effectively prevent the direct flow of electrons between the positive and negative electrodes, thereby preventing internal short circuits in the battery. Polyvinyl chloride has good thermal stability to a variety of chemicals. It has good tolerance and is suitable for a variety of electrolyte systems. At the same time, it is easy to process and shape during the preparation of the diaphragm, which can improve the production efficiency of the diaphragm. In particular, because polyvinyl chloride contains chlorine, it has a certain flame retardancy, which can improve the safety of the battery; polyethylene terephthalate has excellent mechanical strength and can withstand the pressure and stress during the battery cycle. At the same time, it has a high melting point and good thermal stability, and can maintain structural stability at higher temperatures; the chemical structure of polystyrene makes it easy to modify by co-chemical or physical methods to introduce specific functions, such as conductivity or flame retardancy.
[0067] Furthermore, the binder is any one of polyvinylidene chloride, polyacrylic acid, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl alcohol, and polytetrafluoroethylene.
[0068] Specifically, polyvinylidene chloride has extremely strong chemical stability and solvent resistance, can remain stable in the battery electrolyte, and is not easily corroded or dissolved, thereby ensuring the structural characteristics of the electrode. At the same time, it can remain stable within a wide voltage range and will not react with the battery electrode, thereby ensuring the electrochemical performance and safety of the battery; polyacrylic acid is hydrophilic and can promote the wetting of the electrolyte in the motor material to improve the transmission efficiency of lithium ions. At the same time, it also has good adhesion and elasticity, and can adapt to the volume changes of the electrode material during the battery cycle to maintain the structural integrity of the electrode; carboxymethyl cellulose is easily soluble in water, which is convenient for the preparation of battery slurry to reduce production costs. At the same time, it can also improve the dispersibility of the active substance in the slurry to ensure the electrode material. The uniformity of the material coating process; styrene-butadiene rubber has good elasticity and can adapt to the volume change of the electrode material during the charge and discharge cycle and maintain the mechanical stability of the electrode. At the same time, styrene-butadiene rubber is also a relatively low-cost binder, which is conducive to cost saving; polyvinyl alcohol has good film-forming properties and can form a uniform protective layer on the surface of the electrode material to improve the stability of the electrode. At the same time, it has good adhesion with the electrode material, which helps to maintain the structural integrity of the electrode during the battery cycle; polytetrafluoroethylene has extremely high chemical stability and can remain stable in harsh battery environments, improving the safety of the battery. At the same time, due to its excellent heat resistance, it can maintain structural stability at high temperatures and avoid safety problems caused by increased temperature.
[0069] Further, the ratio of solute to solvent is 1:1 to 1:9.
[0070] Specifically, within a reasonable range of solute-to-solvent ratios, the viscosity and fluidity of the slurry can be optimized. When a large amount of solvent is present, the fluidity of the slurry is enhanced, which is beneficial to the uniform mixing of the slurry and the subsequent coating process. The appropriate viscosity ensures that the slurry is neither too thin, resulting in a too thin coating layer that affects battery performance, nor too viscous, thereby increasing the difficulty of coating and energy consumption. At the same time, a high proportion of solvent can ensure that the solid particles are fully dispersed and reduce agglomeration, thereby improving the activity of the electrode material and the uniformity of the battery.
[0071] Furthermore, the thickener is any one of sodium alginate, mica, carboxymethyl cellulose and polyurethane.
[0072] Specifically, sodium alginate can significantly increase the viscosity of the slurry, improve its rheological properties, keep a stable shape during the coating process, and not easily flow, thereby improving coating accuracy and uniformity; at the same time, sodium alginate is easily soluble in water and is suitable for the preparation of water-based slurries, which is beneficial to environmental protection and cost control. In addition, sodium alginate can form a stable gel-like structure in the slurry, which helps to maintain the uniform dispersion of the slurry components and reduce agglomeration; the flaky structure of mica can form an interlaced network structure in the slurry, increase the mechanical strength of the slurry, make it not easy to break during the coating process, and improve the structural integrity of the electrode material; in addition, mica has good thermal stability, which can maintain the stability of the slurry performance in the high temperature environment of the battery, avoiding the degradation of the slurry performance due to the increase in temperature. Mica also has good electrical insulation properties, It helps to improve the safety of the battery; carboxymethyl cellulose can increase the viscosity and stability of the slurry by forming a hydrogen bond network, adjust the rheology of the slurry, and make it easy to coat. At the same time, it can also improve the dispersibility of solid particles in the slurry, and at the same time form a bond with the particle surface, enhance the adhesion and stability of the slurry, and facilitate the uniform coating of the electrode material; polyurethane has excellent elasticity, can adapt to the volume change of the electrode material during the charge and discharge process, maintain the stability of the electrode structure, and improve the cycle performance of the battery; polyurethane can form a good bond with a variety of electrode materials, enhance the bonding force between electrode materials, and improve the mechanical strength of the electrode; the introduction of polyurethane can adjust the rheology of the slurry, so that it has good fluidity and stability during the coating process, reduce defects, and improve the coating quality. These materials are selected as thickeners before modification mainly because they can effectively adjust the rheological properties of the battery slurry, improve the viscosity and stability of the slurry, and ensure the performance requirements of the battery slurry during preparation and coating.
[0073] Furthermore, the proportion of the composite slurry is: the mass percentage of the modified polymer layer microspheres is 70%-99.99%, the mass percentage of the binder is 0%-10%, the mass percentage of the thickener is 0%-10%, and the mass percentage of the dispersant is 0%-10%.
[0074] Specifically, a high proportion of modified polymer layer microspheres ensures that the diaphragm has sufficient porosity, optimizes the transmission path of lithium ions, and thus improves the ionic conductivity and electrochemical performance of the battery. Although the modified polymer layer microspheres occupy a large proportion, an appropriate amount of binder can significantly enhance the bonding force between the microspheres and improve the overall mechanical strength and stability of the diaphragm. This enhancement helps the structural integrity of the diaphragm during the battery cycle and reduces the diaphragm breakage or deformation caused by mechanical damage or pressure changes, thereby improving the cycle life and safety of the battery; the presence of thickeners and dispersants can adjust the rheological properties of the composite slurry to make it have a suitable The viscosity and fluidity of the coating process are improved to facilitate the coating process, while reducing defects in the coating process, such as bubbles, uneven coating layers, etc., and improving the coating quality and efficiency of electrode materials; dispersants can improve the dispersibility of solid particles in the slurry, ensure the uniform distribution of modified polymer layer microspheres, binders and thickeners in the slurry, avoid agglomeration, and improve the uniformity and consistency of the diaphragm, which is beneficial to improving the performance and stability of the battery; by reducing the use of other additives (binders, thickeners, dispersants), and using modified polymer layer microspheres as the main component, the high performance requirements of the diaphragm can be ensured while reducing production costs. This helps to achieve dual optimization of cost-effectiveness and battery performance in large-scale production.
[0075] The present application also provides a method for preparing a diaphragm, which is applied to the above-mentioned lithium battery. The method includes preparing a third isolation layer. The method for preparing the third isolation layer includes:
[0076] Mixing the modified polymer microspheres, the dispersant and the solvent to obtain a first mixed slurry;
[0077] Adding a binder and a thickener to the first mixed slurry and mixing them to obtain a second mixed slurry;
[0078] adding the binder again into the second mixed slurry;
[0079] The second mixed slurry is coated on the surface of the second insulating layer, and dried and cut within a preset temperature range to obtain a modified polymer composite layer to obtain a third insulating layer. The preset temperature range is 37° C. to 85° C.
[0080] Specifically, first prepare a first mixed slurry: select (70%-99.99%) of modified polymer microspheres (such as PP, PE microspheres), select (0%-10%) of a dispersant (such as carboxymethyl cellulose CMC or polyurethane PU), add the above materials to a solvent (such as water, NMP, DMSO), the proportion of the solvent is to ensure that other components are fully dispersed, and use a stirring device to stir the mixture evenly to form a first mixed slurry;
[0081] Prepare a second mixed slurry: add 0%-10% by weight of a binder (such as PVDF, PAA, PTFE) and 0%-10% by weight of a thickener (such as sodium alginate, mica) to the first mixed slurry, and stir again to ensure that all components are evenly mixed to form a second mixed slurry;
[0082] Secondary addition of binder: A small amount of binder can be added again as needed to further enhance the bonding force between the microspheres, which helps to improve the mechanical stability and structural integrity of the diaphragm;
[0083] Diaphragm coating and treatment: Use coating equipment to evenly coat the second mixed slurry on the surface of the second isolation layer (such as PP or PE polymer layer) to ensure the thickness and uniformity of the coating layer; dry the coated diaphragm within a preset temperature range (37°C to 85°C) to remove the solvent and solidify the binder and thickener in the slurry to form a stable diaphragm structure; after drying, cut the diaphragm to meet the size requirements of the battery cell to obtain the final modified polymer composite layer.
[0084] The preparation of the first mixed slurry ensures the uniform dispersion of the modified polymer microspheres and the dispersant in the solvent, which is conducive to the formation of a uniformly distributed diaphragm layer, improves the stability of the diaphragm, and avoids agglomeration during the coating process; by adding the binder and the thickener to the first mixed slurry to form the second mixed slurry, the viscosity and fluidity of the slurry can be effectively adjusted, making it more suitable for the coating process, ensuring the smooth coating process, reducing defects, and improving production efficiency; the secondary addition of the binder can further enhance the bonding force between the microspheres, which is conducive to the structural integrity of the diaphragm during the battery charge and discharge cycle, and reducing the damage to the diaphragm caused by mechanical stress or electrochemical reaction; by precisely controlling the slurry ratio and coating process, the porosity of the diaphragm can be optimized to ensure the effective transmission of lithium ions, while maintaining the insulation properties of the diaphragm and improving the electrochemical performance of the battery; the preset coating and drying temperature range (37°C to 85°C) helps to maintain the rheological properties of the slurry, ensure its uniform coating on the diaphragm surface, avoid cracks or holes during the drying process, and improve the uniformity and consistency of the diaphragm. The modified polymer composite layer obtained through the above steps can effectively improve the electrochemical performance, mechanical stability and safety of the battery.
[0085] The following Table 1 is a comparison result between the diaphragm prepared in this application and the common ceramic diaphragm in the prior art:
[0086] Table 1
[0087]
[0088]
[0089] As shown in Table 1, it can be clearly concluded that the thickness of the diaphragm in this application is consistent with that of ordinary ceramic materials, and the surface density, puncture strength, tensile strength TD, and elongation TD are all higher than those of ordinary ceramic materials, and the tensile strength MD, elongation MD, thermal shrinkage MD, and thermal shrinkage TD are all lower than those of ordinary ceramic materials. Among them, the increase in the surface density of the diaphragm means that the mass of the diaphragm per unit area increases, which can improve the mechanical strength and thermal stability of the diaphragm, making it less likely to have internal structural damage in the case of a short circuit, thereby effectively preventing the conduction of the short-circuit current and reducing the short-circuit temperature rise. The enhanced puncture strength of the diaphragm ensures that during the manufacture and use of the battery, even if there is an unexpected puncture or extrusion, the diaphragm is not easily damaged, which further improves the safety of the battery and reduces the probability of short-circuit accidents. The increase in tensile strength TD (cross-sectional direction) strengthens the lateral strength of the diaphragm during the battery winding process, helps the diaphragm to remain stable inside the battery, reduces the possibility of internal micro-short circuits, and thus indirectly controls the temperature rise of the battery in a short-circuit state. Tensile strength MD, elongation MD reduction (machine direction) The reduction in tensile strength and elongation makes it less likely for the diaphragm to produce mechanical deformation and displacement inside the battery, which is conducive to maintaining the structural stability inside the battery cell and reducing thermal runaway caused by internal structural changes, thereby reducing the temperature rise during short circuit. Reduce the thermal shrinkage performance of the diaphragm (MD and TD directions) to ensure that the diaphragm will not shrink due to temperature increase when the battery is running or short-circuited, avoid direct contact between the positive and negative electrodes to cause a short circuit, and effectively control the temperature rise during the short circuit process. The reduction in elongation in the TD direction, in synergy with the enhancement of tensile strength TD, enhances the stability of the diaphragm inside the battery, reduces the risk of thermal runaway caused by diaphragm deformation, and thus helps control the temperature rise during short circuit.
[0090] like Figure 3 As shown, the solid line represents a lithium battery using the diaphragm prepared by the present application, and the dotted line represents a lithium battery not using the diaphragm prepared by the present application. It can be clearly seen that the lithium battery equipped with the diaphragm prepared by the present application can reduce the temperature rise of the battery to within 50°C when a short circuit occurs, compared with the prior art, thereby providing effective protection for the lithium battery.
[0091] In summary, the diaphragm in the present application solves the problem of excessive short-circuit temperature rise of the capsule endoscope lithium battery. When the battery is short-circuited, it can respond quickly to reduce the short-circuit temperature rise to less than 50°C. In addition, the present application forms a diaphragm by providing an isolation layer with different materials, which can provide battery short-circuit protection without introducing an external device, without changing the battery volume and without reducing the overall energy density of the battery.
[0092] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0093] Unless otherwise specifically stated, the relative arrangement, numerical expressions and numerical values of the parts and steps set forth in these embodiments do not limit the scope of the present invention. Meanwhile, it should be understood that, for ease of description, the sizes of the various parts shown in the accompanying drawings are not drawn according to the actual proportional relationship. The technology, method and equipment known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology, method and equipment should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters represent similar items in the following drawings, and therefore, once a certain item is defined in an accompanying drawing, it does not need to be further discussed in subsequent drawings.
[0094] In the description of the present invention, it is necessary to understand that the directions or positional relationships indicated by directional words such as "front, back, up, down, left, right", "lateral, vertical, perpendicular, horizontal" and "top, bottom" are usually based on the directions or positional relationships shown in the drawings. They are only for the convenience of describing the present invention and simplifying the description. Unless otherwise specified, these directional words do not indicate or imply that the devices or elements referred to must have a specific direction or be constructed and operated in a specific direction. Therefore, they cannot be understood as limiting the scope of protection of the present invention. The directional words "inside and outside" refer to the inside and outside relative to the contours of each component itself.
[0095] For ease of description, spatially relative terms such as "above", "above", "on the upper surface of", "above", etc. may be used here to describe the spatial positional relationship between a device or feature and other devices or features as shown in the figure. It should be understood that spatially relative terms are intended to include different orientations of the device in use or operation in addition to the orientation described in the figure. For example, if the device in the accompanying drawings is inverted, the device described as "above other devices or structures" or "above other devices or structures" will be positioned as "below other devices or structures" or "below other devices or structures". Thus, the exemplary term "above" can include both "above" and "below". The device can also be positioned in other different ways (rotated 90 degrees or in other orientations), and the spatially relative descriptions used here are interpreted accordingly.
[0096] In addition, it should be noted that the use of terms such as "first" and "second" to limit components is only for the convenience of distinguishing the corresponding components. If not otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of the present invention.
[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A diaphragm, characterized in that: include: A first isolation layer (3), used for contacting with the positive electrode of the lithium battery; A third isolation layer (4), used for contacting with the negative electrode sheet of the lithium battery; A second isolation layer (5) is provided between the first isolation layer (3) and the third isolation layer (4); Wherein, the first isolation layer (3) comprises a ceramic material, the third isolation layer (4) comprises a modified polymer composite layer material, and the second isolation layer (5) comprises a polymer layer material.
2. The diaphragm according to claim 1, characterized in that The third isolation layer (4) is obtained by coating a composite slurry on the surface of the second isolation layer (5).
3. The diaphragm according to claim 2, characterized in that The components of the composite slurry include a solvent and a solute, wherein the solute includes chemically modified polymer layer microspheres, a binder, a thickener, and a dispersant; The method for modifying the thermal sensitivity of the polymer layer microspheres is surface modification or changing the degree of polymerization of the polymer layer microspheres.
4. The diaphragm according to claim 3, characterized in that The method for modifying the adhesiveness of the adhesive is to perform any one of copolymerization modification and cross-linking treatment on the adhesive; The method for modifying the thickening property of the thickener is to change the molecular weight of the thickener or to modify the structure of the thickener; The method for modifying the dispersibility of the dispersant is to adjust any one of the initiator and the chain transfer agent of the dispersant, wherein the initiator and the chain transfer agent are used to change the molecular weight and molecular weight distribution of the dispersant.
5. The diaphragm according to claim 3, characterized in that The polymer layer microspheres are any one of polypropylene, polyethylene, polyvinyl chloride, polyethylene terephthalate and polystyrene.
6. The diaphragm according to claim 3, characterized in that The binder is any one of polyvinylidene chloride, polyacrylic acid, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl alcohol and polytetrafluoroethylene.
7. The diaphragm according to claim 3, characterized in that The ratio of the solute to the solvent is 1:1 to 1:
9.
8. The diaphragm according to claim 3, characterized in that The thickener is any one of sodium alginate, mica, carboxymethyl cellulose and polyurethane.
9. The diaphragm according to claim 3, characterized in that The proportion of the composite slurry is as follows: the mass percentage of the modified polymer layer microspheres is 70%-99.99%, the mass percentage of the binder is 0%-10%, the mass percentage of the thickener is 0%-10%, and the mass percentage of the dispersant is 0%-10%.
10. A method for preparing a diaphragm, characterized in that: The method is applied to the diaphragm according to any one of claims 1 to 9, and the method comprises: A third isolation layer is prepared, wherein the preparation method of the third isolation layer comprises: Mixing the modified polymer microspheres, the dispersant and the solvent to obtain a first mixed slurry; Adding a binder and a thickener into the first mixed slurry and mixing them to obtain a second mixed slurry; adding the binder again into the second mixed slurry; The second mixed slurry is coated on the surface of the second isolation layer, and dried and cut within a preset temperature range to obtain a modified polymer composite layer to obtain the third isolation layer, and the preset temperature range is 37° C. to 85° C.
Citation Information
Patent Citations
Lithium ion battery composite diaphragm and preparation method and application thereof
CN104157811A
Polymer particle, diaphragm containing polymer particle and lithium ion battery
CN112795184A
Capsule endoscope battery
CN116014377A
Diaphragm, electrochemical device and electronic device
CN116565458A
Capsule endoscope battery
CN116864827A
Cited By
Separator and preparation method therefor
EP4790819A1
Separator and preparation method therefor
WO2026129565A1